Quantificação das perdas técnicas da distribuição em condições distorcidas - Braz, Lara (2019)
Energy losses in electric distribution utilities are classified as technical and non-technical losses. The non-technical losses are associated with the commercial management of the distribution utilities and they are partially recognized in energy tariffs. The technical losses, in turn, are intrinsically associated with the energy transportation process and they are fully recognized in the tariff composition for each distribution utility. In Brazil, the technical losses are determined by power flow studies considering the medium and low voltage systems, according to ANEEL recommendations, presented in Module 7 of PRODIST. However, the current procedures do not consider the energy losses resulting from the flow of harmonic currents generated by the nonlinear loads, which represent almost the totality of the electrical loads worldwide. Thus, this work aims to consider the inclusion of harmonic losses in the technical losses of the distribution utilities, as well as to quantify, albeit in an estimated way, the effect of such consideration. Several case studies are performed considering the use of OpenDSS software for the medium and low voltage systems of a specific electric distribution utility. For this purpose, the technical losses were calculated in two different ways: (i) considering only the fundamental component of the current, as currently considered by ANEEL and (ii) including the harmonic components of line currents, obtained from a measurement campaign carried out on hundreds of consumers from different electric utilities. The results obtained show that the harmonic currents, in fact, represent a significant additional share in the technical losses of the distribution utilities, highlighting a possible imbalance in the energy tariff composition, with the consequent numerical increase of the non-technical losses in detriment to the technical losses.